Color Features of Object Names - Y A Chudina (Peoples' Friendship University of Russia (RUDN University), 2014)
The results of the experimental research of subjective discrimination of color object features, specified by the nouns of the Russian language, have been described in the article. The received data were interpreted in terms of E.N. Sokolov and Ch.A. Izmailov's spherical model of differentiating stimuli. The subjective model of color discrimination derived on the basis of nouns comparison corresponds with the spherical model of discrimination of the color features represented by the Russian language adjectives.